Employee Performance Optimization with The Approach Leadership and Work Motivation - Teguh Setiawan Wibowo; Amelia (Optima Science, 2023)
The purpose of this research is to find out the optimization of employee performance with a leadership and work motivation approach. The type of research used in this research is survey research. The objects in the research are leadership, work motivation, and employee performance. The research subjects were employees of CV. Contractor Trust. The population in this study were all employees of CV. The mainstay of contractors is 39 people. The technique used in this study is a census technique, so the sample is 39 employees. The type of data used is primary data obtained through questionnaires, and secondary data in the form of CV archives. Contractor Trust. The research period was carried out within the last 6 months of 2022. The data collection method used the questionnaire method, and the documentation method. Test the research instrument using the validity and reliability of the data. Data analysis techniques using descriptive statistical analysis, classical assumption test, multiple regression test, and hypothesis testing. The results of the study show that 1) leadership has a significant effect on employee motivation; 2) leadership has a significant effect on employee performance; 3) work motivation has a significant effect on employee performance; and 4) leadership mediated by work motivation has a significant effect on employee performance.